Pengembangan Media Pembelajaran Interaktif Berbasis Android untuk Meningkatkan Keterampilan Lompat Jauh Gaya Jongkok Siswa SMA Negeri 3 Makassar - Suriah Hanafi (Jurnal Inovasi Olahraga, 2026)
Purpose of the study: This research aims to develop and test the effectiveness of interactive Android-based learning media for long jump material using the squat style at SMA Negeri 3 Makassar. Materials and methods: The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of 36 students of class X MIPA selected through purposive sampling technique. Data collection techniques included expert validation sheets (media and material experts), student practicality questionnaires, and long jump skill tests. Data were analyzed using descriptive statistics and N-gain test. Results: The results showed that: (1) the validation of media experts obtained a score of 4.42 with a "very valid" category, and material experts obtained a score of 4.58 with a "very valid" category; (2) the practicality test obtained a score of 4.35 with a "very practical" category; and (3) the effectiveness test showed an N-gain value of 0.72 with a "high" category, indicating a significant improvement in students' long jump skills. Conclusions: These findings confirm that the developed interactive learning media is valid, practical, and effective in improving students' long jump squat style skills. The implication of this research provides an alternative digital-based learning innovation for physical education teachers in delivering long jump material.